2021
DOI: 10.2991/ahsr.k.211105.012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activities of Gel Extract Marine Sponges (Axinella Carteri) to White Mice Male

Abstract: Indonesia, especially the Kepulauan Riau, has very wide marine waters, and is rich in natural resources and marine biota diversity. One of the marine biota that has the potential to be developed is the marine sponge as an anti-inflammatory because it contains the flavonoid compound which is able to inhibit the cyclooxygenase enzyme that functions in the biosynthesis of prostaglandins. The purpose of this study was to determine whether marine sponge extract had anti-inflammatory activity against white male mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…has also shown an abundance of alkaloids, terpenoids, and sterols, which may be responsible for its antiinflammatory properties (De Silva et al, 2018). Another anti-inflammatory study carried out using Axinella carter originated from Riau Islands also reported an abundance of alkaloids, flavonoids, terpenoids, and saponins (Mayefis et al, 2021). Thus, the bioactivities observed during the study may be the effect of a single compound, or a combination of many compounds, or both.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…has also shown an abundance of alkaloids, terpenoids, and sterols, which may be responsible for its antiinflammatory properties (De Silva et al, 2018). Another anti-inflammatory study carried out using Axinella carter originated from Riau Islands also reported an abundance of alkaloids, flavonoids, terpenoids, and saponins (Mayefis et al, 2021). Thus, the bioactivities observed during the study may be the effect of a single compound, or a combination of many compounds, or both.…”
Section: Resultsmentioning
confidence: 93%
“…It is well accepted that marine sponges harbour an array of bioactive compounds that may be responsible for their anti-inflammatory properties (Mehbub et al, 2014). Flavonoids have been shown to inhibit enzymes involved in inflammation, including cyclooxygenase and lipoxygenase, while alkaloids have been shown to reduce the synthesis or effect of some pro-inflammatory cytokines, as well as limit histamine release and nitric oxide generation (Mayefis et al, 2021). The genus Axinella is particularly known for having a variety of metabolites, including bromo compounds, cyclopeptides, polyethers, sterols, and terpenes (Yalçin, 2007).…”
Section: Resultsmentioning
confidence: 99%